Maternal exposure to PM2.5 during pregnancy and asthma risk in early childhood: Consideration of phases of fetal lung development. Issue 2 (2nd April 2021) - Hazlehurst, Marnie F.; Carroll, Kecia N.; Loftus, Christine T.; Szpiro, Adam A.; Moore, Paul E.; Kaufman, Joel D.; Kirwa, Kipruto; LeWinn, Kaja Z.; Bush, Nicole R.; Sathyanarayana, Sheela; Tylavsky, Frances A.; Barrett, Emily S.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Increasingly studies suggest prenatal exposure to air pollution may increase risk of childhood asthma. Few studies have investigated exposure during specific fetal pulmonary developmental windows. Objective: To assess associations between prenatal fine particulate matter exposure and asthma at age 4. Methods: This study included mother–child dyads from two pregnancy cohorts—CANDLE and TIDES—within the ECHO-PATHWAYS consortium (births in 2007–2013). Three child asthma outcomes were parent-reported: ever asthma, current asthma, and current wheeze. Fine particulate matter (PM2.5 ) exposures during the pseudoglandular (5–16 weeks gestation), canalicular (16–24 weeks gestation), saccular (24–36 weeks gestation), and alveolar (36+ weeks gestation) phases of fetal lung development were estimated using a national spatiotemporal model. We estimated associations with Poisson regression with robust standard errors, and adjusted for child, maternal, and neighborhood factors. Results: Children (n = 1, 469) were on average 4.3 (SD 0.5) years old, 49% were male, and 11.7% had ever asthma; 46% of women identified as black and 53% had at least a college/technical school degree. A 2 μg/m 3 higher PM2.5 exposure during the saccular phase was associated with 1.29 times higher risk of ever asthma [95% confidence interval (CI): 1.06, 1.58]. A similar association was observed with current asthma (risk ratio 1.27, 95% CI: 1.04, 1.54), but not current wheeze (risk ratio 1.11, 95% CI: 0.92, 1.33). Effect estimates for associations during other developmental windows had CIs that included the null. Conclusions: Later phases of prenatal lung development may be particularly sensitive to the developmental toxicity of PM2.5 .